Petrology, geochemistry and geological significance of andesites of Jintan gold orefield in Eastern Tianshan, Xinjiang - Zhu, Y.; Wang, T.; Huang, C.; Dai, T.; Yang, L.; Chong, K.Y.; Du, G. (Central South University of Technology, 2017)
A set of andesites closely related to the Au mineralization was developed from Jintan Gold Deposit. Element concentration of the andesites and geochemical correlation analysis were made. According to the results, both the zircons structure of the andesites and ω(Th)/ω(U) (0.30-1.02, ω is element mass fraction) indicate that the zircons are the origin of magma, and the zircon U-Pb age is (303.65±4.8) Ma, which stands for the formation age of andesites. The ω(SiO2) of andesites is from 54.29% to 69.05%, ω(Al2O3) is from 11.27% to 19.46% and ω(K2O+Na2O) is from 2.46% to 6.81%, ω(MgO) is from 3.60% to 10.45% and Mg index changes from 46 to 66. The light rare earth elements (LREE) of andesites is enriched, and the differentiation between LREE and HREE is obvious. Eu of the vast majority of the sample shows moderate negative anomaly (δω(Eu)=0.44-0.77), while Ce shows slight negative anomalies (δω(Ce)=0.93~0.98). It is enriched in large ion lithophile elements (such as K, Rb, Ba, Th and U), and depleted in high field strength elements (such as Nb and Ti). The magma undergones the fractional crystallization and partial melting. The andesites are probably formed by partial melting of mantle wedge, which is metasomatized by subducting fluids when the Kanggurtag ocean southward subducts, oceanic crust dehydrates and subducts into the mantle wedge. Meanwhile the magma undergones fractional crystallization, and suffers significant continental crust material contamination. Based on comprehensive analysis, subduction of the Kangguer ocean is still underway in the East Tianshan mountain region at the time of Late Carboniferous.